Blockchain for Enhancing Data Traceability in Digital Supply Chain Management - Hayatun Nufus; Bambang Hermansah; Ratna Tri Hari Safariningsih; Shesilia Wibowo; Noah Rangi (IAIC Bangun Bangsa, 2026)
In recent years, the complexity of global supply chains has increased the need for transparent, secure, and traceable data management systems. As a background to this study, conventional supply chain databases often suffer from data fragmentation, lack of interoperability, and vulnerability to manipulation, which hinder real-time decision-making and trust among stakeholders. The main objective of this research is to explore how blockchain technology can enhance data provenance tracking and integrity within digital SCM systems. To achieve this, a hybrid research method combining literature review, case study analysis, and system prototype simulation was conducted to examine the effectiveness of blockchain-based record tracking frameworks. The method integrates smart contracts and distributed ledger technology to record, verify, and share data across multiple supply chain entities. The results reveal that blockchain implementation significantly improves data transparency, reduces information asymmetry, and enhances trust across different supply chain participants. Furthermore, the findings indicate that the decentralized nature of blockchain minimizes data tampering risks and supports compliance with international traceability standards. In conclusion, this research demonstrates that blockchain provides a robust foundation for digital SCM by strengthening data lineage tracking, security, and accountability, ultimately contributing to a more resilient and efficient supply chain ecosystem.